Data redundancy of blockchain systems in construction projects - Lu, Weisheng; Wu, Liupengfei; Chen, Chen (Frontiers in Built Environment, 2024)
Industrial stakeholders have complained that current blockchain systems are too expensive, particularly in temporary endeavours like construction projects. However, while researchers have examined blockchain system structure among inter-firm organizations in construction, little research has considered the data redundancy of these systems. This research, therefore, provides insight by modelling data redundancy in construction project blockchain systems. We conduct a series of laboratory experiments on a Hyperledger Fabric blockchain system, discovering that the data volume of a blockchain system grows proportionally with the size of the files to be uploaded, the number of peer nodes in the network, and the frequency of blockchain operations in construction, regardless of the block size or how the peers are dispersed in different construction organizations. Beyond identifying the factors that determine data redundancy of a blockchain system, this research provides a basis for researchers to explore the optimization of blockchain storage and the impacts of blockchain system data redundancy in construction projects. In practical terms, the proposed data redundancy model 2 in this research provides a reference for users in construction who aim to build blockchain systems.